Permeability of Sand-Based Cemented Backfill under Different Stress Conditions: Effects of Confining and Axial Pressures - Cunli Zhu; Jixiong Zhang; Nan Zhou; Meng Li; Yaben Guo (Geofluids)
Sand-based cemented backfill (SBCB) mining technology is instrumental in utilizing coal resources buried under the water bodies. SBCB is exposed to the long-term action of mining-induced stresses in the goaf and groundwater permeating via microcracks along the rock strata. Studying the permeability evolution of SBCB under varying stress states is crucial for protecting coal and water resources below the aquifer. This study is focused on the influence law of different stress states on the SBCB permeability exposed to groundwater, which was tested under different axial and confining pressures using a laboratory seepage meter, particle size analyzer, scanning electron microscope (SEM), and X-ray diffractometer (XRD). Best-fitting quadratic polynomials linking the SBCB permeability with confining and axial pressures, respectively, were obtained via statistical processing of test results. The permeability gradually dropped within the elastic range as the confining and axial pressures increased. Moreover, an increase in the confining pressure caused a more dramatic reduction in the SBCB permeability than the axial pressure. Finally, the SBCB seepage mechanism under different stress states was revealed based on the particle size analysis, XRD patterns, and SEM microstructure. These findings are considered instrumental in substantiating safe mining of coal resources below the water bodies and above the confined groundwater.